2009
DOI: 10.4314/as.v8i1.44113
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of Nutrient Source On The Elemantal Composition Of Irrigated Garlic

Abstract: The effect of five nutrient (fertilizer) sources on garlic (Allium sativum L.) grown under irrigation in Bauchi state was in vestigated. Irrigation was scheduled at 25% management allowable deficit, giving an irrigation interval of 4 days and gross application depth of 56 mm of water per application. The nutrient sources were NPK fertilizer (15:15:15), wood ash, poultry manure, and fermented cow dung slurry, while the control was zero fertilization. The composition of crop samples grown under application of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It has a fine particulate structure, good moisture-holding capacity, and contains nutrients readily taken up by plants. Allium sativum has a low capacity to absorb nutrients from soils due to a relatively underdeveloped root system (Babatunde et al, 2009). Hence, for proper plant nourishment and high-quality yield, an adequate and balanced supply of readily available nutrients is essential in cultivating garlic.…”
Section: Introductionmentioning
confidence: 99%
“…It has a fine particulate structure, good moisture-holding capacity, and contains nutrients readily taken up by plants. Allium sativum has a low capacity to absorb nutrients from soils due to a relatively underdeveloped root system (Babatunde et al, 2009). Hence, for proper plant nourishment and high-quality yield, an adequate and balanced supply of readily available nutrients is essential in cultivating garlic.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic and most species of the genus Allium have a low capacity to absorb nutrients from soils due to a relatively underdeveloped root system. Therefore, for proper plant development and high-quality yields, an adequate, balanced supply of readily available nutrients is essential in cultivating A. sativum [14]. One of the increasingly used organic fertilisers is vermicompost, which is characterised by the slow release of macronutrients and microelements into the soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…Organic fertilisers are an excellent alternative to mineral fertilisation. It was shown that fertilising garlic with wood ash and fermented manure produced garlic with low moisture content in the bulbs, high pungency, and higher mineral content [14]. The positive effect of manure compost on selected garlic traits (e.g., plant length, number of leaves, bulb weight, number of cloves and weight of cloves) was shown by Shafeek et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Organic inputs are often proposed as alternatives to mineral fertilizers. Organic fertilizers like wood ash, poultry manure, and fermented slurry were reported to produce garlic having low moisture content, high pungency, and higher mineral composition (Babatunde et al, 2009). However, the traditional organic inputs such as crop residues, and animal manures cannot meet crop nutrient demand over large areas because of the limited quantities available, the low nutrient content of the materials, and the high labour demands for processing and application (Pratap et al, 2011).…”
Section: Introductionmentioning
confidence: 99%